Revitalizing the Bicol College Livelihood Programs at Barangay Kilicao in Daraga, Albay - Vicente Fernandez (JPAIR, 2019)
Livelihood is one of the ways of helping people alleviate poverty. This action research determined the causes of the temporary closure of the projects implemented in terms of (1) attitude of the participants, (2) organizer, and (3) financial support and the recommended development plan. This action research employed the descriptive method of research and utilized the focused-group discussion as the primary source of data and as the main data gathering instrument. The findings revealed that the participants failed to demonstrate a positive attitude, no facility in terms of sanitation and proper product handling, no complete equipment, and materials needed, failure of the organizer to fully support the projects and not enough financial assistance from the institution to sustain the livelihood projects. As recommended, the livelihood projects should be revitalized to achieve its sustainability, the organizer spearhead to conduct seminars and workshops on livelihood trainings, regularly monitor an asses the activities, and prepare a five-year livelihood development plan.